EFFECTIVENESS OF TAX SANCTIONS AND TAXPAYER UNDERSTANDING OF INDIVIDUAL TAXPAYER COMPLIANCE AT KPP PRATAMA JAKARTA PULOGADUNG - Said Khaerul W,; Desy Amaliati Setiawan,; M.Aditis Alfarizi, (Juremi: Jurnal Riset Ekonomi, 2024)
This study aims to determine the effectiveness of tax sanctions on individual taxpayer compliance at KPP Pratama Jakarta Pulogadung and to determine the effectiveness of taxpayer understanding of individual taxpayer compliance at KPP Pratama Jakarta Pulogadung. The population in this study were individual taxpayers registered at KPP Pratama Jakarta Pulogadung. In this study, the sample used was 100 respondents by determining the number of samples using the Slovin formula and taking based on the Purposive sampling method. Data collection was carried out by distributing questionnaires to respondents with measurements using a Likert scale. This study uses multiple linear analysis with the help of SPSS27 software. The results of this study indicate that the variables of tax sanctions and taxpayer understanding have a significant influence on individual taxpayer compliance